The inclusion of handicapped children in regular schools: reflection about the role of the Occupational therapy - Rocha, Eucenir Fredini; Castiglioni, Maria do Carmo; Vieira, Rita de Cássia (Revista de Terapia Ocupacional da Universidade de São Paulo, 2001)
This article is a reflection about the problem of the inclusion of handicapped child into a regular school and the role of Occupational Therapy. Furthermore, it describes the experience of including handicapped children who use the REATA ambulatory (Laboratory of Studies about Rehabilitation and Assistive Technology) from the course of Occupational Therapy at FMUSP, in public schools, developed from 1995 to 2000. The choice for a methodology of participative action facilitated talking about the involved issues and overcoming prejudice and fear related to this activity. The out come was the creation of a room in pedagogical support of children who attend regular schools, as well as the inclusion of about 49% of the children from ambulatory, whether having grave or moderate disabilities, in regular rooms.